Scene of Fighting Tigers on a Sasanian Plate from Mes ‘Aynak. Notes on the Composition - Skupniewicz, Patryk (Acta Archaeologica Lodziensia, 2020)
The article discusses, from formal perspective, the mounted hunting scene on the Kushano-Sasanian silver plate found in Mes Aynak in Afghanistan. The scene represents the model related to other Sasanian silverware, however with significant variances. When compared the scene to other models defined by Author, conclusion is made that except for several “canonical” layouts, Sasanian toreuts, allowed themselves a dose of freedom in combining them. This phenomenon seems to be related to peripheries of the Sasanian Empire and model of a sword-wielding rider in combat with large felines while holding an object in outstretched left hand was defined as originating from Kushanshahr and combining Assyrian and Achaemenid formulae of men killing beasts with mounted archer/lancer layouts popular in Sasanian silver.